2019
DOI: 10.1002/chem.201805473
|View full text |Cite
|
Sign up to set email alerts
|

Mapping Aldehyde Dehydrogenase 1A1 Activity using an [18F]Substrate‐Based Approach

Abstract: Aldehyde dehydrogenases (ALDHs) catalyze the oxidation of aldehydes to carboxylic acids. Elevated ALDH expression in human cancers is linked to metastases and poor overall survival. Despite ALDH being a poor prognostic factor, the non‐invasive assessment of ALDH activity in vivo has not been possible due to a lack of sensitive and translational imaging agents. Presented in this report are the synthesis and biological evaluation of ALDH1A1‐selective chemical probes composed of an aromatic aldehyde derived from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(16 citation statements)
references
References 38 publications
0
16
0
Order By: Relevance
“…The procedure was adapted from that previously reported by our group. 21 (3 × 0.40 mL). The precursor 4 (10.0 mg, 28.8 µmol) was added to the reaction vessel as a solution in anhydrous DMSO (1 mL).…”
Section: Automated Radiosynthesis Of [ 18 F]1 On the Ge Fastlabmentioning
confidence: 99%
See 3 more Smart Citations
“…The procedure was adapted from that previously reported by our group. 21 (3 × 0.40 mL). The precursor 4 (10.0 mg, 28.8 µmol) was added to the reaction vessel as a solution in anhydrous DMSO (1 mL).…”
Section: Automated Radiosynthesis Of [ 18 F]1 On the Ge Fastlabmentioning
confidence: 99%
“…In order to circumvent these inherent limitations, us and others have proposed the use of positron emission tomography (PET) as an alternative to fluorescence-based imaging. 21,22 We have recently reported that [ 18 F]N-ethyl-6-(fluoro)-N-(4-formylbenzyl)nicotinamide -[ 18 F]1 -has excellent affinity and isozyme selectivity for ALDH1A1 in cancer cells but is rapidly oxidised to its corresponding carboxylic acid in the blood when administered at tracer doses. 21 Here, we employed an enzyme-cleavable pro-drug strategy to increase the blood stability of our ALDH1A1targeted radiotracer.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Many cancer cells upregulate aldehyde dehydrogenases in response to this oxidative stress, which mediates aldehyde detoxification (22). The enzymatic activity of aldehyde dehydrogenase 1A1 has recently been quantified with a novel substrate-based radiotracer (23). Using a complementary strategy, Kirby et al developed 18 F-NA3BF3 for the imaging of total aldehydic load through radiotracer-aldehyde complex formation (24).…”
Section: Imaging the Tumor Antioxidant Responsementioning
confidence: 99%